Hybrid modeling of diffusive shock acceleration in collisionless shocks in multispecies plasma - Kropotina, J. A.; Bykov, A. M.; Ermolina, V. E.; Osipov, S. M.; Romansky, V. I.
Diffusive shock acceleration (DSA) is a very effcient mechanism of high energy particle acceleration in heliosphere, supernova remnants, stellar winds and gamma-ray bursts. We present microscopic simulation of particle injection and diffusive shock acceleration which is performed with 3D divergence-conserving second-order accurate hybrid code \Maximus". Hydrogen plasma with admixture of various heavy ions is considered. The injection process is found to start through shock re ection for both hydrogen an heavier ions. However, the refection process depends on charge-to-mass ratio. While hydrogen ions re ection appears at shock ramp and is governed by the cross-shock potential, the re ection of ions with greater A=Z proceeds deeper down- stream via gyration in perpendicular magnetic field component. The heavy ions appear to inject into the DSA preferentially, but this chemical enhancement saturates with growing A=Z. The protons injection efficiency is estimated within various approaches, and it is shown that about 20% of initial ow energy goes into accelerated particles.
Keywords: Astronomy